APPLICATION OF THE WORD SQUARE LEARNING MODEL TO IMPROVE LEARNING ACTIVITY AND STUDENT LEARNING OUTCOMES AT SMAN 11 PANGKEP - Adie Maksar; Suwardi Annas; Rego Devilla (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
In this increasingly modern era, it requires teacher professionals to be able to cultivate varied learning models in each subject so that students are not saturated while following the existing learning process. This study aims to improve student activity and learning outcomes through a word square learning model at SMA Negeri 11 Pangkep. This research is a type of classroom action research (PTK). The subjects of the study were class XI students totaling 33 students. Data collection techniques are carried out by means of observation, tests, and documentation. Data analysis techniques use analytical descriptive analysis. The results showed that 1) The percentage of student activity increased each cycle. Where in the first cycle student activity is in the less active category and increases in cycle II in the very active category, 2) The completeness of student learning outcomes increases every cycle. Where in cycle I it was 33% with an average learning outcome of 66.9 and increased in cycle II by 81% with an average learning outcome of 85.7. Thus, the conclusion is that the application of the word square learning model can increase the activeness and learning outcomes of economics subjects for class XI students of SMA Negeri 11 Pangkep.